Development of Students' Soft Skills Through Activity Management in The Department of Islamic Education Management - Tihul, Inan; Khotimah, Fitri Balqis Khusnul; Alfani, Ilzam Hubby Dzikrillah; Al'Asror, Rohimin; Khusnadin, Muhammad Hafidz (The Magister of Islamic Education IAIN Pontianak, 2025)
This study aims to analyze the role of event management in transforming the soft skills of students in the Islamic Education Management (MPI) Study Program at Sunan Kalijaga State Islamic University. Soft skills are non-technical competencies that are important for students' readiness to enter the workforce, such as communication, teamwork, time management, and leadership. Using a qualitative approach with a case study method, this research involved 63 students actively involved in organizing more than ten academic and student activities during the 2023/2024 academic year. Data was collected through in-depth interviews, participatory observation, and activity documentation. The research findings indicate that students' direct involvement in every stage of event management—from planning, coordination, implementation, to evaluation—significantly contributes to strengthening their interpersonal and intrapersonal skills. The integration of Islamic values such as honesty, responsibility, and work ethic reinforces students' character and professionalism in the context of teamwork and leadership. Institutional support in the form of faculty mentoring and infrastructure also plays a role in optimizing this experience-based learning process. This study concludes that event management can serve as an effective contextual learning strategy for the holistic development of students' soft skills. Recommendations are provided to integrate soft skills enhancement into the curriculum, expand interdisciplinary programs, and strengthen faculty training to ensure optimal guidance.